1991
DOI: 10.3109/00016489109137406
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Mechanisms Induced by High Oropharyngeal Airway Resistance in Rats

Abstract: Acid base balance changes were observed during 72 h following bilateral nasal obstruction in rats. Mouth breathing caused acute respiratory acidosis and marked aerophagia, leading to spontaneous death of the experimental animal 80 to 90 h postoperatively. Stenotic oropharyngeal airway, due to palatal-epiglottic approximation, is supposed to be responsible for respiratory insufficiency in the nose obstructed rats. The compensatory changes in respiratory mechanics caused by high oropharyngeal airway resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…One (of six) 27-week-old Eda Ta mice had two solitary foci of bronchiolitis associated with inhaled fragments of hair; and six 13-week-old Edar dlJ/dlJ mice had unremarkable lungs. In rodents, increased resistance to nasopharynx airflow can result in swallowing of air into the stomach and intestines (aerophagia) (19) and over a two year period we observed eight instances of clinical abdominal bloating in our HED colony mice; seven of eight cases were in adult mice >7-weeks-old; three in Eda Ta males at 3-, 8- and 18-weeks of age respectively, and five cases in 12-15 week-old male and female Edar dlJ/dlJ mice. Post mortem examination revealed a gas filled stomach, small intestine and caecum (Figure 8I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One (of six) 27-week-old Eda Ta mice had two solitary foci of bronchiolitis associated with inhaled fragments of hair; and six 13-week-old Edar dlJ/dlJ mice had unremarkable lungs. In rodents, increased resistance to nasopharynx airflow can result in swallowing of air into the stomach and intestines (aerophagia) (19) and over a two year period we observed eight instances of clinical abdominal bloating in our HED colony mice; seven of eight cases were in adult mice >7-weeks-old; three in Eda Ta males at 3-, 8- and 18-weeks of age respectively, and five cases in 12-15 week-old male and female Edar dlJ/dlJ mice. Post mortem examination revealed a gas filled stomach, small intestine and caecum (Figure 8I).…”
Section: Resultsmentioning
confidence: 99%
“…One of the pathological sequelae in HED mice was sporadic clinical aerophagia. In adult rats, increased resistance to airflow by experimental obstruction of the nasal passages causes aerophagia (19) and spontaneous nasal/nasopharynx disease in HED mice may have the same effect.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the nasal passages from irritant gas exposure in obligate nose breathing animals can result in forced oral breathing. As forced oral breathing can by itself produce respiratory distress, hypoxemia, lung injury, and even death (Ramadan, 1983; Kalogjera et al, 1991), it can represent a confounding effect that would not be observed in humans. In addition, the large surface area of nasal epithelium in obligate nose breathing animals produces effective scrubbing of inhaled reactive chemicals, thereby lowering the effective dose to which the lung is exposed.…”
Section: Discussionmentioning
confidence: 99%
“…One clear possibility to further test this hypothesis would be to compare food intake in litters that exclusively comprise olfactory‐deprived pups with mixed litters simultaneously comprising untreated, sham and olfactory‐deprived pups. Besides, duration of nursing and olfactory deprivation involves competition between the respiratory and alimentary processes (Kalogjera, Pegan, & Petric, 1991). Respiratory disturbance could thus represent a factor worsening the impact of olfactory deprivation on food intake.…”
Section: Discussionmentioning
confidence: 99%